Development of Rujuku Mobile Learning Apps on Integer Operation Material as Alternative Media - Thoiffatul K. Nisa; Evangelista LW Palupi; Mayang Purbaningrum; Sylvana Novilia Sumarto; Viky H. Putra (Universitas Maritim Raja Ali Haji, 2022)
Since the Covid-19 pandemic in early 2020, Indonesia has implemented distance education by optimizing the use of technology. Therefore, the researcher developed the Rujuku Mobile Learning Apps Development on Integer Operation Material in Class VII SMP/MTs to support the implementation of distance learning during the pandemic. This study aimed to develop the RUJUKU application and determine student responses in learning after using the developed media. This development research uses the ADDIE method. The data collection technique used a questionnaire with data processing techniques analyzed using percentage data analysis techniques. The results showed that RUJUKU was suitable for use, attractive, and easy to use. This is based on the validation results in terms of material, an average of 89.70%, and in terms of media, an average of 88.81%. Student response is quite good, with a percentage of 89.06%. Based on that result, this research significantly impacted the integers' learning process of addition and subtraction operations during this pandemic.